PENGEMBANGAN MODUL PENJUALAN PADA SISTEM INFORMASI E-COMMERCE ULTRA MIKRO BERBASIS WEBSITE - Wulan Seftiani; Irwan Adi Pribadi; Yohana Tri Utami (Jurnal Pepadun, 2022)
Electronic Commerce (E-Commerce) can be interpreted as a technology that is the basic needs of an organization engaged in business. One of the cities in Indonesia where people and business actors have widely used e- commerce as a tool for buying and selling transactions is Bandar Lampung. Most of the people of Bandar Lampung city have used various kinds of social media and e-commerce to market products, including Ultra Micro (UMi) business actors. With so many business actors developing, it is possible to create a new Ultra Mikro (UMi) in Bandar Lampung, with capital ranging from 2-5 million students / female students and housewives domiciled in Bandar Lampung can already establish a private Ultra Micro (UMi) business. The website-based Ultra Mikro e-commerce information system is designed to be able to help the sales activities of Ultra Micro business actors. Features that can be utilized by business actors include product categories, product data, and sales data. Laravel is used as a framework in the construction of this e-commerce system with PHP programming languages and MySQL as databases. The system development methodology used is the Waterfall method. The Waterfall method has several stages, namely communication, planning, modeling, construction, and deployment. Data collection techniques are carried out with literature studies, interviews, as well as analysis of system needs. The results of the research obtained from the development of a website-based Ultra Mikro e-commerce information system are information systems that can improve the quality of customer service and facilitate the marketing of products that can be accessed from anywhere and anytime.